Estado de salud e intención de volver a Estados Unidos en migrantes mexicanos: ¿evidencia de un sesgo de retorno selectivo? - Bojórquez Chapela, Ietza; González Fagoaga, Eduardo; Guillén López, Tonatiuh (El Colegio de México A.C., 2014)
The aim of this study was to explore the association between the intention of remaining in Mexico (versus the intention of returning to the United States), with indicators on the health status of migrants who entered Mexico through the northern border in 2010, for which information from the Northern Border Migration Survey (Emif-N) was used. Those with a worse state of health were less likely to want to return to the United States compared with those in better state of health.